Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.